2001
DOI: 10.1111/j.1744-7348.2001.tb00122.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of soil suppressiveness on various population densities of Heterodera schachtii

Abstract: Infectivity of second-stage juvenile (J2) populations of Heterodera schachtii was assayed with radish. The numbers of J2 in three-day-old seedlings were proportional to the numbers of J2 in two differently textured soils. In a microplot trial with a known H. schachtii-suppressive soil, half of the plots contained untreated suppressive soil, the other half contained the same soil, but methyl iodide-fumigated and therefore conducive. Both soils were infested with cysts introducing the equivalents of 0, 30, 60 or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The bioassay with radish seedlings, previously used for the demonstration of soil suppressiveness against this nematode (21), was useful for testing efficacy of the nematicide. Chemical nematode suppression was detected at the depth of application of the material but not in the nontreated layers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bioassay with radish seedlings, previously used for the demonstration of soil suppressiveness against this nematode (21), was useful for testing efficacy of the nematicide. Chemical nematode suppression was detected at the depth of application of the material but not in the nontreated layers.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the infectivity of J2 of H. schachtii after soil treatment with fosthiazate, composite soil samples of four cores per plot were collected on 12 May and 17 lune and subjected to a modified radish bioassay (21). Briefly, the equivalents of 100 g of soil dry weight were placed in 11-cm-diameter plastic food containers.…”
Section: Experiments With Infestation At Distinct Depth Layers On 23mentioning
confidence: 99%
“…In the nematode-suppressive soil study, transferring a portion of field soil into autoclaved or conducive soil treated by other means is commonly used (Zuckerman et al, 1989;Chen et al, 1996;Westphal & Becker, 2000, 2001aMazzola, 2002;Chen, 2007;Bent et al, 2008). Westphal & Becker (2000) found that a H. schachtiisuppressive soil could establish suppression at a transfer rate of either 1 or 10% field soil; however, it took longer the lower the soil percentage that was transferred.…”
Section: Discussionmentioning
confidence: 98%
“…Unless otherwise noted, each composite sample was divided into twelve subsamples equivalent to 50 g dry soil each. Three subsamples were used for cyst extraction by density centrifugation [27]. Single soil samples (50 g) were placed in a bucket with a 250-µm aperture sieve as the bottom to wash off fine soil particles with tap water.…”
Section: Cyst Extractionmentioning
confidence: 99%